A postmarket safety comparison of 2 vaccination strategies for measles, mumps, rubella and varicella in Italy. Issue 3 (3rd March 2016) - Cocchio, Silvia; Zanoni, Giovanna; Opri, Roberta; Russo, Francesca; Baldo, Vincenzo; ,
ABSTRACT: It is strategically important to monitor the safety profile of vaccination schedules in order to achieve and maintain high levels of coverage. We analyzed the cohort of individuals actively invited for measles, mumps, rubella and varicella (MMRV) vaccination in the Veneto region (north-east Italy) from 8/1/2013 to 7/31/2014, assessing the onset of adverse events (AE) relating to 2 different vaccination strategies for MMRV (MMR+V vs MMRV). During the vaccination session at 14 months old, parents were given a form for recording local and systemic reactions to vaccinations for 4 weeks afterwards. Overall, 12, 288 forms were returned, and 84.6% of them were included in this analysis (5, 130 relating to MMR+V and 5, 265 to MMRV); 37.3% of the sample reported no AEs, with no difference between the 2 groups. Local reactions were more common in the MMR+V group (9.6% vs 2.9%; RR 3.33; 95% CI 2.79–3.98), while there was no difference in general reactions between the 2 groups (50% MMR+V vs 52% MMRV). The events most often reported were "fever <39.5°C, " which was more frequently associated with the MMRV strategy (p<0.001), and "skin blotches and marks, " which occurred more often in the MMR+V group (p<0.001). Reports of "fever ≥39.5°C" were equally distributed between the 2 groups. Sixteen cases of febrile seizures were reported (0.14% in the MMR+V group and 0.17% in the MMRV group). Similar safety profiles were identified for the 2 vaccination strategies. Although the method used to record reactions to vaccination demanded considerable resources, it enabled important information to be collected on parents' perception of the AEs occurring in response to their child's vaccination.